2017
DOI: 10.1111/pce.12959
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lima bean terpene synthases in rice enhances recruitment of a beneficial enemy of a major rice pest

Abstract: Volatile terpenoids play a key role in plant defence against herbivory by attracting parasitic wasps. We identified seven terpene synthase genes from lima bean, Phaseolus lunatus L. following treatment with either the elicitor alamethicin or spider mites, Tetranychus cinnabarinus. Four of the genes (Pltps2, Pltps3, Pltps4 and Pltps5) were up-regulated with their derived proteins phylogenetically clustered in the TPS-g subfamily and PlTPS3 positioned at the base of this cluster. Recombinant PlTPS3 was able to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…as repellents) against a range of insect pests e.g. aphids, leafhoppers, stinkbugs (Hegde et al 2011; Moraes et al 2009; Oluwafemi et al 2011; Sobhy et al 2017), and in indirect defence via recruitment of natural enemy parasitic wasps (Bruce et al 2008; Li et al 2017; Moraes et al 2009; Tamiru et al 2011). Furthermore, Magalhães et al (2012) suggested that cotton boll weevils, Anthonomus grandis recognize the physiological stage of host cotton plants via information on the amount of DMNT and TMTT released by cotton plants.…”
Section: Discussionmentioning
confidence: 99%
“…as repellents) against a range of insect pests e.g. aphids, leafhoppers, stinkbugs (Hegde et al 2011; Moraes et al 2009; Oluwafemi et al 2011; Sobhy et al 2017), and in indirect defence via recruitment of natural enemy parasitic wasps (Bruce et al 2008; Li et al 2017; Moraes et al 2009; Tamiru et al 2011). Furthermore, Magalhães et al (2012) suggested that cotton boll weevils, Anthonomus grandis recognize the physiological stage of host cotton plants via information on the amount of DMNT and TMTT released by cotton plants.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of DMNT and TMTT in attracting parasitoids of herbivores have spurred growing interest in improving natural plant defence via the genetic engineering of DMNT and TMTT formation. C. chilonis were more attracted to rice plants with overexpression of TPS3 and TPS4 genes of P. lunatus, which released more DMNT and TMTT than wild-type rice plants (Li et al, 2017). Transgenic Lotus japonicus plants with the TPS2 gene of P. lunatus produced TMTT, and the specialist P. persimilis was strongly attracted to herbivore-damaged L. japonicas expressing this gene (Brillada et al, 2013).…”
Section: Cpr Was Necessary For the Catalytic Action Of Ghcyp82lsmentioning
confidence: 97%
“…Lima bean and thale cress (Arabidopsis thaliana) plants release homoterpenes to attract predatory mites when attacked by spider mites (Lee et al, 2010;Mumm et al, 2008). Rice (Oryza sativa) plants produce homoterpenes highly attractive to females of Cotesia chilonis after attack by the striped rice stem borer Chilo suppressalis (Li et al, 2017). Campoletis sonorensis and Cotesia marginiventris also respond to homoterpenes released by Spodoptera littoralis-infested cotton (Gossypium herbaceum) or maize (Zea mays) plants (Gouinguen e et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For industrial agriculture, such highly volatile and chemically unstable compounds cannot be formulated in a cost‐effective manner, so use of GM to generate crops that can more effectively use these semiochemicals is appealing. Already the crop plant rice has been genetically modified to produce increased levels of DMNT and TMTT, and in laboratory studies increased the foraging behaviour of the parasitoid, C. chilonis , Braconidae, attacking the rice pest Chilo suppressalis , Crambidae . This study is a prelude to attempting control of the brown planthopper , Nilaparvata lugens, Delphacidae, the major rice pest.…”
Section: Crop Protection From Secondary Plant Metabolism By Metabolicmentioning
confidence: 99%
“…Already the crop plant rice has been genetically modified to produce increased levels of DMNT and TMTT, and in laboratory studies increased the foraging behaviour of the parasitoid, C. chilonis, Braconidae, attacking the rice pest Chilo suppressalis, Crambidae. 29 This study is a prelude to attempting control of the brown planthopper, Nilaparvata lugens, Delphacidae, the major rice pest.…”
Section: Plant Defence-related Semiochemicals Delivered By Gmmentioning
confidence: 99%